Theological Meaning Don’t There Any Other God Before Me In The Exodus 20:3 - Anjai Silalahi; Bobby Kurnia Putrawan (Journal of Religious and Socio-Cultural, 2020)
Basically, there are still many Christians who do not have a correct understanding of the monotheistic God and what it is related to the first Law of God. Because this lack of understanding often occurs among Christians who practice polytheism, syncritism and others who do not please God. Do not have other gods before Me (Ex. 20: 3), which is a very basic thing that must be understood well, in order to carry out true worship of the true God. This study aims to provide a concrete explanation of the importance of knowing the correct understanding of there should be no other God before Me (Ex. 20: 3). This study uses the (library research) method using books and other reading materials. The approach used is descriptive which focuses on the meaning of the phrase do not have another god before Me according to Exodus 20: 3. Pada dasarnya masih banyak orang Kristen yang belum memiliki pemahaman yang benar tentang Tuhan yang tauhid dan apa kaitannya dengan Hukum Tuhan yang pertama. Karena kurangnya pemahaman ini sering terjadi di antara orang-orang Kristen yang mempraktikkan politeisme, sinkritisme, dan orang-orang lain yang tidak menyenangkan Tuhan. Jangan ada tuhan lain di hadapan-Ku (Keluaran 20: 3), yang merupakan hal yang sangat mendasar yang harus dipahami dengan baik, agar dapat melaksanakan penyembahan yang benar kepada Tuhan yang benar. Penelitian ini bertujuan untuk memberikan penjelasan yang konkrit tentang pentingnya mengetahui pemahaman yang benar bahwa tidak ada Tuhan yang lain di hadapan-Ku (Keluaran 20: 3). Penelitian ini menggunakan metode (studi pustaka) dengan menggunakan buku dan bahan bacaan lainnya. Pendekatan yang digunakan adalah deskriptif yang menitikberatkan pada makna kalimat tidak memiliki tuhan lain dihadapan-Ku menurut Keluaran 20: 3.